2013
DOI: 10.1103/physreva.88.033622
|View full text |Cite
|
Sign up to set email alerts
|

Excitation spectrum of a toroidal spin-1 Bose-Einstein condensate

Abstract: We calculate analytically the Bogoliubov excitation spectrum of a toroidal spin-1 Bose-Einstein condensate that is subjected to a homogeneous magnetic field and contains vortices with arbitrary winding numbers in the mF = ±1 components of the hyperfine spin. We show that a rotonlike spectrum can be obtained, or an initially stable condensate can be made unstable by adjusting the magnitude of the magnetic field or the trapping frequencies. The structure of the instabilities can be analyzed by measuring the part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…When the decay in GS1 is driven by the density mode, diagonalization of the full Bogoliubov operator shows that close to instability there appears a roton-like structure that is linked to the nucleation of excitations in the internal surface, similarly to what has been predicted in single components [46] and spinor condensates [47]. This roton-like structure induces a minimum in the Dopplershifted excitation spectrum at finite , which leads to the decay of the persistent current through phase-slips (vortices) when the lowest frequency becomes negative.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…When the decay in GS1 is driven by the density mode, diagonalization of the full Bogoliubov operator shows that close to instability there appears a roton-like structure that is linked to the nucleation of excitations in the internal surface, similarly to what has been predicted in single components [46] and spinor condensates [47]. This roton-like structure induces a minimum in the Dopplershifted excitation spectrum at finite , which leads to the decay of the persistent current through phase-slips (vortices) when the lowest frequency becomes negative.…”
Section: Discussionmentioning
confidence: 54%
“…In BECs they have been predicted not only in static situations such as in dipolar condensates [50], but also in the presence of currents in the ground state, such as in spin-orbit coupled condensates [51,52] or the results presented here and in Refs. [46,47]. In the dipolar case, the roton mode touching zero is generally associated to density-wave or supersolid configurations (see the recent experiment [53]).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The population imbalance and fixed phase relation between multiple components bring persistent flows novel stability features [18][19][20][21][22]. It has been found that rich phase diagram and interesting collective excitations can exist in interacting two-component [23][24][25][26] and three-component [27][28][29] toroidal BECs.…”
Section: Introductionmentioning
confidence: 99%
“…The previous theoretical works regarding multicomponent systems (two-component Bose gases [40][41][42][43][44] and spinor BECs [45,46]) in a ring trap concern the stability of persistent currents. Other important properties, including metastability under external rotation, have also been thoroughly investigated theoretically [47,48] and experimentally [7,8,10] for scalar BECs.…”
Section: Introductionmentioning
confidence: 99%